Access to water and space in Romanian freshwater aquaculture - Erzsebet Olariu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 11th Edition, 2020)
Aquaculture falls within the scope of the Common Fisheries Policy (CFP) using the advantage of common market organization and financial measures as in integral part of this policy. Despite all these advantages, the results obtained from European aquaculture did not live up to expectations. Given that it is necessary to protect aquatic resources in the wild, aquaculture presents a viable alternative, especially with regard to the favorable social aspect by creating jobs. The European Commission, after consultation, identifies four priority guidelines for achieving sustainable aquaculture: reducing the complexities of administrative procedures, facilitating access to space through coordinated spatial planning, increasing the competitiveness of the sector, supporting the conditions of fair competition. In terms of spatial planning the asking is to elaborate maps with spatial planning and find areas where other activities and aquaculture may coexist. This paper studies how access to space in aquaculture in Romania is works.
Keywords: Q22; Q15; Q24; Q01; 330; aquaculture; space; sustainable; competitiveness